promoting the use of tree and crop biodiversity for sustainable production systems - CGIAR Research Program on Water, Land and Ecosystems (2020)
in collaboration with 2 districts and Jimma University, the project aims at developing new tools based on seeds for needs and diversity for restoration toolkit